ANALYSIS OF MODERN CUTTING EQUIPMENT APPLIED IN THE SEWING INDUSTRY - SYROTENKO, OKSANA; DITKOVSKA ОLESYA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The range of modern cutting equipment for the sewing industry is very diverse. It includes the simplest manual disk cutting knives, industrial equipment of a more complex level - mobile machines with round knife and straight knife cutting machines, stationary band knife cutting machines, and ultra-complex semi-automated and automated cutting complexes. A separate group consists of laser and plasma installations, among the newest cutting equipment types. These types of equipment are distinguished by their capacity, speed, cutting height, and cost. The scope of their application is due to the type of activity of the enterprise, its capacity, and the raw material used to manufacture clothing. The price of cutting equipment is usually due to its capacity and reliability and depends on the manufacturer. Technical characteristics of cutting equipment vary widely, which allows the selection of different models of the given raw material, its thickness, density, and other physical and mechanical properties of materials. Automated cutting complexes provide vacuum compression of the flooring, which ensures high accuracy and speed of cutting the flooring and high accuracy of the details themselves - which makes it ultra-relevant. However, automated cutting machines and complexes, as well as laser installations, are quite expensive and available only for large-capacity enterprises. The profitability of the equipment depends on the volume of production and capacity of sewing enterprises and factories. Accordingly, low-capacity enterprises should use the round knife and straight knife cutting machines, for medium-capacity enterprises - and stationary band knife machines, for high-capacity enterprises - semi-automatic and automatic cutting complexes. Of course, its price is no less important when choosing equipment. Therefore, low-capacity enterprises should use lower-cost equipment from less well-known manufacturers. For high-capacity sewing factories with high production rates, recommended to use expensive equipment from leading market leaders.